Vacuolar ATPase depletion affects mitochondrial ATPase function, kinetoplast dependency, and drug sensitivity in trypanosomes - Baker, Nicola; Hamilton, Graham; Wilkes, Jonathan M; Hutchinson, Sebastian; Barrett, Michael P; Horn, David (Proceedings of the National Academy of Sciences - PNAS, 2015)
Kinetoplastid parasites cause lethal diseases in humans and animals. The kinetoplast itself contains the mitochondrial genome, comprising a huge, complex DNA network that is also an important drug target. Isometamidium, for example, is a key veterinary drug that accumulates in the kinetoplast in African trypanosomes. Kinetoplast independence and isometamidium resistance are observed where certain mutations in the F1-γ-subunit of the two-sector F1Fo-ATP synthase allow for Fo-independent generation of a mitochondrial membrane potential. To further explore kinetoplast biology and drug resistance, we screened a genome-scale RNA interference library in African trypanosomes for isometamidium resistance mechanisms. Our screen identified 14 V-ATPase subunits and all 4 adaptin-3 subunits, implicating acidic compartment defects in resistance; V-ATPase acidifies lysosomes and related organelles, whereas adaptin-3 is responsible for trafficking among these organelles. Independent strains with depleted V-ATPase or adaptin-3 subunits were isometamidium resistant, and chemical inhibition of the V-ATPase phenocopied this effect. While drug accumulation in the kinetoplast continued after V-ATPase subunit depletion, acriflavine-induced kinetoplast loss was specifically tolerated in these cells and in cells depleted for adaptin-3 or endoplasmic reticulum membrane complex subunits, also identified in our screen. Consistent with kinetoplast dispensability, V-ATPase defective cells were oligomycin resistant, suggesting ATP synthase uncoupling and bypass of the normal Fo-A6-subunit requirement; this subunit is the only kinetoplast-encoded product ultimately required for viability in bloodstream-form trypanosomes. Thus, we describe 30 genes and 3 protein complexes associated with kinetoplast-dependent growth. Mutations affecting these genes could explain natural cases of dyskinetoplasty and multidrug resistance. Our results also reveal potentially conserved communication between the compartmentalized two-sector rotary ATPases.